EVALUASI PROGRAM MAGANG INDUSTRI KREATIF SMP SEKOLAH ALAM BOGOR - Samiah Samiah (Jurnal Manajemen Pendidikan, 2018)
Theoretically, the result of this research hopefully can give scientific contribution toward development of science, especially science of education, give suggestion to another school about evaluation of program for better quality of education, also by way of evaluation for secondary school of Sekolah Alam Bogor for being more effective internship program. The research use qualitative method. Data were got by doing interview, observation, and check list. The data were used for evaluating internship program of creative industry for more effective program implementation. Subject of this research are students and teachers who participated in internship program of creative industry also the owner of the place. Based on the data which were got, it can be concluded that internship program of creative industry can improve knowledge, skills, and positive attitude of students with supporters factors: monitoring of the principal, the role of the teacher, the role of the owner of internship place, and communication between the school and internship place.